A case report of complete remission of acute myeloid leukemia combined with DNMT3A, FLT3-TKD, and IDH2 gene mutations and active pulmonary tuberculosis treated with homeharringtonine + venetoclax + azacytidine - Ji, Lin; Yang, Wei; Xu, Xiao-feng; Xu, Ya-qing (Frontiers in Medicine, 2023)
In March 2022, a 58-year-old man was admitted to the local hospital for nausea and vomiting. His blood routine indicated that he had leukocytosis and anemia. The patient was diagnosed with acute myeloid leukemia (AML)-M5b accompanied by DNMT3A, FLT3-TKD, and IDH2 mutations, chest CT revealed pulmonary tuberculosis (TB). Acid-fast bacillus (AFB) was detected in sputum. The patient then received anti-TB treatment with isoniazid + rifampicin + pyrazinamide + ethambutol. On April 8, he was transferred to our hospital's Hematology Department after three consecutive negative sputum smears. He was administered the VA (Venetoclax + Azacytidine) regimen of anti-leukemia treatment and also received levofloxacin + isohydrazide + pyrazinamide + ethambutol anti-TB treatment. After one course of VA therapy, there was no remission in the bone marrow. Therefore, the patient received the HVA (Homeharringtonine + Venetoclax + Azacytidine) regimen of anti-leukemia treatment. On May 25, the bone marrow smear revealed that the original mononuclear cells were 1%. Moreover, bone marrow flow cytometry revealed the absence of any abnormal cells. mNGS showed DNMT3A (mutation rate 44.7%), but no mutations were detected in FLT3-TKD and IDH2. The patient then received the HVA regimen three consecutive times, resulting in complete remission. Repeated chest CT examinations revealed progressive regression of pulmonary TB foci, no AFB was detected in the sputum. This AML patient with DNMT3A, FLT3-TKD, and IDH2 mutations and active TB is difficult to treat. It is very necessary for him to administer prompt anti-leukemia treatment under the premise of active anti-TB treatment. The HVA regimen is effective for this patient.